Effects of climate on pollination networks in the West Indies - González, Ana M. Martín; Dalsgaard, Bo; Ollerton, Jeff; Timmermann, Allan; Olesen, Jens M.; Andersen, Laila; Tossas, Adrianne G. (Journal of tropical ecology, 2009)
We studied the effect of climate on the plant-pollinator communities in the West Indies. We constructed plots of 200 m × 5 m in two distinct habitats on the islands of Dominica, Grenada and Puerto Rico (total of six plots) and recorded visitors to all plant species in flower. In total we recorded 447 interactions among 144 plants and 226 pollinator species. Specifically we describe how rainfall and temperature affect proportional richness and importance of the different pollinator functional groups. We used three measures of pollinator importance: number of interactions, number of plant species visited and betweenness centrality. Overall rainfall explained most of the variation in pollinator richness and relative importance. Bird pollination tended to increase with rainfall, although not significantly, whereas insects were significantly negatively affected by rainfall. However, the response among insect groups was more complex; bees were strongly negatively affected by rainfall, whereas dipterans showed similar trends to birds. Bird, bee and dipteran variation along the climate gradient can be largely explained by their physiological capabilities to respond to rainfall and temperature, but the effect of climate on other insect pollinator groups was more obscure. This study contributes to the understanding of how climate may affect neotropical plant-pollinator communities.